Studies of the Mechanism for Enhanced Cell Surface Factor VIIa/Tissue Factor Activation of Factor X on Fibroblast Monolayers after Their Exposure to N-Ethylmaleimide - The Le, Dzung; Rapaport, Samuel I; Vijaya Mohan Rao, L (Thrombosis and Haemostasis, 1994)
Fibroblast monolayers constitutively expressing surface membrane tissue factor (TF) were treated with 0.1 mM N-ethylmaleimide (NEM) for 1 min to inhibit aminophospholipid translocase activity without inducing general cell damage. This resulted in increased anionic phospholipid in the outer leaflet of the cell surface membrane as measured by the binding of 125I-annexin V and by the ability of the monolayers to support the generation of prothrombinase. Specific binding of 125I-rVIIa to TF on NEM-treated monolayers was increased 3- to 4-fold over control monolayers after only brief exposure to 125I-rVIIa, but this difference progressively diminished with longer exposure times. A brief exposure of NEM-treated monolayers to rVIIa led to a maximum 3- to 4-fold enhancement of VIIa/TF catalytic activity towards factor X over control monolayers, but, in contrast to the binding studies, this 3- to 4-fold difference persisted despite increasing time of exposure to rVIIa. Adding prothrombin fragment 1 failed to diminish the enhanced VIIa/TF activation of factor X of NEM-treated monolayers. Moreover, adding annexin V, which was shown to abolish the ability of NEM to enhance factor X binding to the fibroblast monolayers, also failed to diminish the enhanced VIIa/TF activation of factor X. These data provide new evidence for a possible mechanism by which availability of anionic phospholipid in the outer layer of the cell membrane limits formation of functional VIIa/TF complexes on cell surfaces.